HAZOP Study Based on ANFIS Layer of Protection Analysis in Unit Kiln PT. Semen Indonesia Factory Tuban - Prasetyo, Henry; Musyafa’, Ali (Institut Teknologi Sepuluh Nopember, 2015)
Process safety and risk assessment are vital demand for any industry to characteristic hazard and their for personnel, environment and loss of money. Unit Kiln are part of industrial cement, operated at high temperature and high pressure. Security so the process must be maintained so as not to pose a hazard with a high risk. Risk matrix is a very useful tool to estimate of process or equipment that helps decision making process. HAZOP (Hazard and Operability) study is one method to know risk assessment. Thus ANFIS logic method for risk assessment is selected as a new and efficient way to industry resource management. This study generally include quantitative review of possible accident, based on previous accident experiences that may occur in a typical process in unit kiln. For the HAZOP study the possible exist to limit failure in case definition and risk modeling to only accident that may include fire, exploitation and toxic effect risks. Consequence a ANFIS risk matrix is based on Layer Of Protection Analysis (LOPA) and HAZOP Study procedure for analyzing. The result from this research that have be done study HAZOP unit kiln PT. Semen Indonesia Factory Tuban and also know risk impact and get SIL rating for this plant.